Graphical user interface for Humanoid Head Amir-II - Shafie, Amir Akramin; Alias, Mohd Farid; Alang Md Rashid, Nahrul Khair (2010)
This paper presents the development of graphical user interface (GUI) for Humanoid Head Robot Amir-II. The GUI serves as a monitoring tool for the robot operation which includes the visual input from a webcam as its eye and the positioning of the Dynamixel AX-12 robot actuators. Matlab Graphical User Interface Development Environment (Matlab GUIDE) is used in developing the GUI which enables Matlab codes on face tracking, facial expression recognition and servo callbacks to be integrated within the GUI. The humanoid head is programmed to detect a human face within its view and automatically follow the tracked face through the movement of its neck joints. There is also a dedicated control panel within the GUI to capture the facial expression screenshots and save them into the database with their related expression labels. © 2010 IEEE.